The Detective Value of Magnetically Controlled Robotic Capsule Endoscopy in Patients With Suspected Small Intestinal Disease - Chen, Xiao-Yu; Da, Wei; Liang, Rui; Fan, Hui-Ning; Yi, You-Cai; Chen, Ming; Qin, Huang-Wen; Zhang, Jing; Zhu, Jin-Shui (Frontiers in Medicine, 2021)
Objective: To explore the detective value of magnetically controlled robotic capsule endoscopy (MCRCE) in patients with suspected small intestinal disease. Patients and Methods: In total, 1,802 patients with suspected small intestinal disease and negative gastroenteroscopy from Shanghai Jiao Tong University Affiliated Sixth People's Hospital were examined with MCRCE, and the data were collected for further analysis. Results: Among the 1,802 patients who were examined with MCRCE, 974 were diagnosed with small intestinal disease, reaching a positive detection rate of 54.1%. The five most common conditions that were detected include non-specific enteritis in 722 cases (40.1%), small intestinal ulcers in 87 cases (4.8%), abnormal small bowel evacuation in 45 cases (2.5%), small intestinal bleeding in 33 cases (1.8%), and small intestinal yellow spots in 31 cases (1.7%). The running time of the capsules in the small intestine ranged from 85–437 min, with an average of 210.24 ± 89.08 min. No complications, such as intestinal obstruction or capsule retention, were observed in all patients. Conclusion: MCRCE is a safe and non-invasive endoscopic examination with a highly accurate detection rate for small intestinal diseases.